Terapi Okupasi pada Perkembangan Motorik Halus Anak Berkebutuhan Khusus - Nurfadillah; Samsualam, Samsualam; Padhila, Nur Ilah; Alam, Rizqy Iftitah (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
In general, every child has different abilities in reaching the stages of motor development, especially fine motor skills. However, not infrequently there are delays or disturbances in its development. Optimal occupational therapy is expected to have an important influence on delays in fine motor development in children. This study aims to determine the effect of occupational therapy on fine motor development in children with special needs in SLB Negeri 1 Makassar. This research is a quantitative research with the type of pre-experimental design research using a one group pretest-posttest research design. The determination of the sample using purposive random sampling method in accordance with predetermined criteria with a sample of 32 respondents. This study used a paired sample t-test statistic with a significance level (ρ < 0.05). From the results of research that has been done, it was found that occupational therapy had an effect on fine motor development ( = 0.001). Based on the results of the study, it showed that there was an effect of occupational therapy on fine motor development in children with special needs in SLB Negeri 1 Makassar. It is recommended that parents who have children with special needs provide occupational therapy independently and continuously or take children to therapists to improve fine motor development in children.